(untitled) (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed at identifying the role of integrative education in Palestine Technical University - Kadoorie to promote entrepreneurship from the point of view of faculty members and the effect of the variables of qualification, gender and experiences, and the point of view of Partner Institutions and the effect of the variables of qualification, gender and company established. The researchers designed two questionnaires: the first is directed to faculty members and consists of (35) items distributed on two scales: integrative education and entrepreneurship, the second questionnaire is directed to partner institutions and consists of (30) items distributed on two scales: integrative education and entrepreneurship. The study sample consisted of (28) from faculty members of integrative education program and (30) from faculty members of integrative education program. They were chosen in a stratified random. The study used the descriptive analytical method. The results showed that the responses of the faculty members of the role of integrative education in Palestine Technical University - Kadoorie to promote entrepreneurship for integrative education and entrepreneurship domains are medium. The results showed that the responses of the partner Institutions of integrative education and entrepreneurship domains are is medium. The results showed that there were no differences from the point of view of faculty members according to the variables of qualification, gender and experiences in all domains. There are no differences from partner institutions according to the variables of qualification, gender and company established of the institution in all domains. The study recommended the necessity of developing relations between companies and universities by signing new agreements between the university and companies that train students.